SPEAKING LEARNING STRATEGIES EMPLOYED BY ENGLISH-MAJORED SOPHOMORES AT COLLEGE OF FOREIGN ECONOMIC RELATIONS - Hoa, Truong Minh; Mien Thao, Phan Thi (VNU Journal of Foreign Studies; Vol 36 No 3DO - 10.25073/2525-2445/vnufs.4558, 2020)
The increasing demand for good communicative skills in a globalized society activates English speaking learning around the world. Specific to the Vietnamese context, after many years of being much exposed to English, most of tertiary students still find it difficult to communicate effectively in realistic situations since they have not yet possessed effective speaking learning strategies (Richards, 2002; Rababa’h, 2005). This study aimed at exploring speaking learning strategies employed by 82 English-majored sophomores at College of Foreign Economic Relations (COFER), Ho Chi Minh City, Vietnam. Mixed-methods design was used for collecting data, involving the two research instruments: a questionnaire and a semi-structured interview. While quantitative data obtained from the questionnaire were analyzed by SPSS 22.0, interview results were thematically analyzed. The findings of the study indicated that the majority of the English-majored sophomores usually utilized both direct and indirect strategies. The most frequently used strategies consisted of structuring or planning of ideas and language input, using dictionary for vocabulary learning, compensating for linguistic limitations by code-switching, nonverbal forms, synonyms, paying attention, deeply breathing, and asking for clarification. However, activating prior knowledge, self-training language input, self-evaluating speaking performance were less frequently used among many students. For implications, teachers should make students aware of the importance of background knowledge and create more opportunities for students to utilize their prior knowledge in their speaking performance, encourage them to frequently practice their listening skills and pronunciation to improve speech quality, and guide them how to assess their own speaking performance.